2022
DOI: 10.1177/13694332221131153
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the bond performance of sea sand coral concrete with FRP bar reinforcement for marine environments

Abstract: The world is rich in marine resources, and the use of seawater, sea sand and coral instead of fresh water, river sand and gravel can solve problems such as the scarcity of traditional materials for marine engineering construction. Additionally, fibre-reinforced polymer (FRP) bars have demonstrated excellent corrosion resistance performance, which can effectively solve the problem of the corrosion of steel in harsh marine environments. To study the bond performance between FRP bars and sea sand coral concrete (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…5 It intensely impacts concrete and construction processes in general. 11,12 Nanotechnology is based on synthesizing nanoparticles with specified characteristics suitable for different applications. 13,14 A nanoparticle is a microscopic particle whose size is measured in nanometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It intensely impacts concrete and construction processes in general. 11,12 Nanotechnology is based on synthesizing nanoparticles with specified characteristics suitable for different applications. 13,14 A nanoparticle is a microscopic particle whose size is measured in nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…SCC has been the most significant development in concrete technology in many ways recently 5 . It intensely impacts concrete and construction processes in general 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Other problems arose in terms of building materials. For example, in traditional construction, some materials are scarce on islands and reefs, and using large ships to transport them long distances can cause damage to the natural environment during construction [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency in the compressive strength of HSC may result in severe structural failures and difficult repairs, as HSC is primarily designed to bear excessive compressive forces (Al-Shamiri et al, 2019). Incorporation of different materials such as fibers (Xie et al, 2021;Shi et al, 2022;Sun et al, 2023), hinges (Huang et al, 2022;Huang et al, 2023a), and special cements (Wang et al, 2022) has also been reported to enhance the properties of cementitious composites. Moreover, researchers are more attentive nowadays to sustainable supplementary cementitious materials for sustainable development (Cao et al, 2019;Arshad et al, 2020;Khan et al, 2021;Ahmad et al, 2023;Lao et al, 2023a;Lao et al, 2023b;Qian et al, 2023;Riaz Ahmad et al, 2023).…”
Section: Introductionmentioning
confidence: 99%